1999
DOI: 10.1021/ic990397b
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic, Structural, and Spectroscopic Studies on the Catecholase Activity of a Dinuclear Copper Complex by Dioxygen

Abstract: Dinuclear copper(II) complexes with the new ligand 1,6-bis[[bis(1-methyl-2-benzimidazolyl)methyl]amino]-n-hexane (EBA) have been synthesized, and their reactivity as models for tyrosinase has been investigated in comparison with that of previously reported dinuclear complexes containing similar aminobis(benzimidazole) donor groups. The complex [Cu2(EBA)(H2O)4]4+, five-coordinated SPY, with three nitrogen donors from the ligand and two water molecules per copper, can be reversibly converted into the bis(hydroxo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
111
0
5

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(127 citation statements)
references
References 40 publications
7
111
0
5
Order By: Relevance
“…Consequently, we propose that in later stages of the catalytic reaction, the oxidation of DTBCH 2 proceeds by a "classic" mechanism, proposed by Krebs et al [1] and Casella et al, [15,16] involving a stoichiometric reaction between the dicopper(II) species and the substrate, leading to the reduced dicopper(I) species. The oxidation of the second equivalent of the substrate by a peroxo-dicopper(II) adduct, formed upon dioxygen binding to the dicopper(I) intermediate, results in the formation of the second molecule of quinone and water as a by-product (Scheme 1, cycle B).…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…Consequently, we propose that in later stages of the catalytic reaction, the oxidation of DTBCH 2 proceeds by a "classic" mechanism, proposed by Krebs et al [1] and Casella et al, [15,16] involving a stoichiometric reaction between the dicopper(II) species and the substrate, leading to the reduced dicopper(I) species. The oxidation of the second equivalent of the substrate by a peroxo-dicopper(II) adduct, formed upon dioxygen binding to the dicopper(I) intermediate, results in the formation of the second molecule of quinone and water as a by-product (Scheme 1, cycle B).…”
Section: Resultsmentioning
confidence: 91%
“…Previously, it has been suggested that the formation of dihydrogen peroxide is the result of either the protonation of the peroxo-dicopper intermediate, or its reaction with catechol, leading to the formation of the reduced dicopper(I) species along with H 2 O 2 . [16,20,41] However, to the best of our knowledge, no actual proof that either of these pathways indeed takes place has been reported, although the formation of dihydrogen peroxide upon treating trans-m-1,2-peroxo-dicopper(II) species with a strong acid is known. [42,43] We thus believe that dihydrogen peroxide is formed as a byproduct during the oxidation of the semiquinone intermediate with dioxygen, when the metal-metal distance within a dicopper(II) complex is too long to allow the binding of the substrate in a didentate bridging fashion.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…observed from Cu 4 L 4 is comparable to those with moderate to high catecholase activities. [8][9][10][11][12][13][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] It is noticeable that the four copper ions are non-coupled in Cu 4 L 4 whereas most model complexes with high catecholase activities are di-or tri-nuclear copper …”
Section: Resultsmentioning
confidence: 99%